Estresse hídrico e salino na germinação e crescimento inicial de plântulas de bauhinia forficata link - Oliveira, Renata Ramayane Torquato (Universidade Federal Rural do Semi-Árido, 2018)
The objective of this work was to evaluate the effect of these stresses, with different osmotic agents, on the germination and initial growth of Bauhinia forficata Link seedlings, in order to evaluate the influence of water and saline stress on seed hydration and germination. The experiment was conducted in the Laboratory of Seed Analysis of the Federal Rural University of the Semi-Arid / UFERSA, in Mossoró-RN. The seeds used were collected in trees located in the Pau Branco Site, rural area of Mossoró-RN. Saline stress simulation was performed using solutions prepared from the dilution of seawater and sodium chloride (NaCl). For the water stress simulation, polyethylene glycol (PEG 6000) and mannitol were used. For both stresses, osmotic potential levels were: 0.0 (control), -0.2; -0.4; -0.6 and -0.8 MPa, with only distilled water being used in the control (0.0 MPa) to moisten the substrate. Seeding was done on paper roll substrate, moistened with the solutions previously mentioned and later incubated in germinator at 25 ° C and photoperiod of 8 hours. The analyzed variables were: germination, germination speed index, shoot and root length, dry shoot and root dry mass. The experimental design was the completely randomized (DIC) in a factorial scheme 4X5, with four types of osmotic agents and five levels of osmotic potentials, with four replicates of 25 seeds each. The germination and initial growth of B. forficata seedlings were affected by water and saline stress from the level of -0.2 MPa, being the osmotic agents that most influenced the germination and vigor of the seeds of B. forficata were PEG 6000 and sea water.
Monografia
Keywords: Salinidade; Déficit hídrico; Vigor; Salinity; Water deficit; Force; CIENCIAS AGRARIAS::AGRONOMIA